Rural Education and Agroecology: pedagogical practice in Botany teaching in an MST´s landless encampments - Jakson da Silva Gonçalves; Sandra Nazaré Dias Bastos; Oscar Ferreira Barros (Universidade Federal do Norte do Tocantins, 2024)
This paper presents a pedagogical experience in Science teaching from the curriculum component Botany which was developed at José Valmeristo School, located in the encampment called Quintino Lira, city of Santa Luzia in Pará (Brazilian state). We aimed to accomplish a pedagogical practice about plant science teaching and trace some discursive possibilities with Agroecology, as well as verify how this practice can collaborate with the teaching changes in the rural school. It is a participatory action research and an experience report about all pedagogical experiences with the students, teachers, and community residents. Throughout these practices, we built a Forest Calendar, a Cutting Production Manual, and the implementation of a small Agroforestry System (AS) in the camp. We discovered some local possibilities of a relationship between Agroecology and Botany teaching, including plant taxonomy, management forms, spacings and intercropping, reforestation, and the AS. When we relate Agroecology and Botany, we noticed that Science teaching transgresses the positivist vision and values traditional knowledge. It causes a reflection on pedagogical practice in the encampment context and MST, which should be closely related to the subject reality, in a dialogued way, so that it can contribute to the changes in their realities.